The effect of the open-ended learning model assisted by animation videos on the mathematical creative thinking ability - Triana; Tanti Jumaisyaroh Siregar (Desimal: Jurnal Matematika, 2025)
Mathematics plays a vital role in developing students’ cognitive and creative thinking skills. However, conventional learning approaches often fall short in stimulating students' mathematical creativity. This study investigates the effect of the open-ended learning model assisted by animation videos on students’ mathematical creative thinking ability. Using a quasi-experimental method with a quantitative approach, the study involved an experimental class taught with open-ended learning and animation videos and a control class with conventional instruction. Results showed that the experimental class outperformed in generating original, flexible, and diverse mathematical ideas. This indicates that integrating open-ended learning with visual animation support positively influences students’ creative mathematical thinking.